Orthodontic Treatment Need and Oral Health Related Quality of Life in Students in Isfahan - Eslamipour, Faezeh; Asgari, Imaneh; Tabesh, Adel (Journal of Dental School, 2019)
Objective: Oral health status particularly maxillofacial disorders in adolescents can affect different aspects of the quality of life. This study aimed to assess the age-related quality of life of students in two age groups of 11-14 years and 14-18 years to evaluate its correlation with orthodontic treatment need in adolescents in Isfahan. Methods: This cross-sectional study was conducted on 11-18 year-old middle school and high- school students. Subjects were selected via two-stage stratified random sampling from 30 schools in different areas of Isfahan city. After examination by two calibrated clinicians, Dental Health Component of Index of Orthodontic Treatment Need (DHC-IOTN) was recorded for all subjects. The Oral Health Related Quality of Life (OHRQoL) was assessed using self-reported Child Perception Questionnaire (CPQ) in 11-14 year-olds and Child Oral Health Impact Profile (COHIP) in 14-18 year-olds. After descriptive analyses, the correlation between the DHC-IOTN and the quality of life score of subjects was assessed using the Spearman’s correlation test and the Mann Whitney U test. Results: A total of 1,227 students were evaluated. The mean and standard deviation (SD) was found to be 18.3 (13.7) for CPQ score in 11-14 year olds. For COHIP score it was found to be 103.6 (18) in 14-18 year olds. A total of 22% from the 604 students examined in the first group, and 17% of 570 students in the second group definitely needed orthodontic treatment. Significant differences existed in the mean quality of life score among the three groups requiring orthodontic treatment in the two age groups (p<0.05). The correlation between the malocclusion severity and quality of life subscales was weak. Conclusion: Based on the results, malocclusion significantly affects the dental function and social and emotional domains of quality of life. However, considering the role of confounders, studies with condition-specific formats of the questionnaire are required to assess the correlation of malocclusions with the quality of life after controlling for other factors.